Fiscal Crisis and Community Development: The Great Recession, Support Networks, and Community Development Corporation Capacity. Issue 1 (2nd January 2017) - Thomson, Dale E.; Etienne, Harley
Abstract: Community development corporations (CDC) are a cornerstone of neighborhood improvement in legacy cities. Yet they face challenges that threaten their financial sustainability, challenges that grew exponentially with the Great Recession. This article examines the impact of the Great Recession on the revenue and survival of CDC in Baltimore, Maryland; Cleveland, Ohio; and Detroit, Michigan. An analysis of financial data from the National Center for Charitable Statistics from 2004 to 2011 highlights issues of industry contraction, revenue concentration and loss, and CDC survival. Interviews and examination of multiple secondary sources of information on CDC activity and support networks in each city further our understanding of the financial results. We find that the CDC industry in all three cities was severely impacted by the Great Recession and that the CDC support networks in each city had a significant intervening effect on the ability of CDC to adapt to the fiscal and service pressures created by the recession. We discuss the implications of the shared trends and the city-specific dynamics for the role of CDC in neighborhood improvement in legacy cities.